The role of attitude of educators towards sexual behaviour of learners in the effectiveness of life skills-based education - Tlakula, Nelly (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2011.